Educar en el buen hablar - Valiente Agreda, Laura (2015)
A theoretical perspective of acquired useful knowledge is being developed for the use of speech in the context where a speaker performs a conversation. On the other hand, the receptor’s under¬standing and his participatory presence in that activity is discussed. Furthermore, the difference between the lexical resource in the use of speech and the lack of these resources in the human conversa¬tion is presented.